Five Characteristics of Youth Unemployment in Europe: Flexibility, Education, Migration, Family Legacies, and EU Policy. (23rd March 2015) - O'Reilly, Jacqueline; Eichhorst, Werner; Gábos, András; Hadjivassiliou, Kari; Lain, David; Leschke, Janine; McGuinness, Seamus; Kureková, Lucia Mýtna; Nazio, Tiziana; Ortlieb, Renate; Russell, Helen; Villa, Paola
Current levels of youth unemployment need to be understood in the context of increased labor market flexibility, an expansion of higher education, youth migration, and family legacies of long-term unemployment. Compared with previous recessions, European-wide policies and investments have significantly increased with attempts to support national policies. By mapping these developments and debates, we illustrate the different factors shaping the future of European labor markets. We argue that understanding youth unemployment requires a holistic approach that combines an analysis of changes in the economic sphere around labor market flexibility, skills attainment, and employer demand, as well as understanding the impact of family legacies affecting increasingly polarized trajectories for young people today. The success of EU policy initiatives and investments will be shaped by the ability of national actors to implement these effectively.